Correction: Ibrahimi et al. Marine Actinobacteria: Screening for Predation Leads to the Discovery of Potential New Drugs against Multidrug-Resistant Bacteria. Antibiotics 2020, 9, 91 - Manar Ibrahimi; Wassila Korichi; Mohamed Hafidi; Laurent Lemee; Yedir Ouhdouch; Souad Loqman (MDPI AG, 2024)
In the original publication, there was a mistake in Figure 1b as published [...]